Leadership and Transformation Towards Smart Cities: Impact on Innovation and Business Performance in the Infrastructure Sector - Harahap, Muhammad Ade Kurnia; Suherlan; Choerudin, Achmad (ADMAN: Journal of Contemporary Administration and Management, 2024)
Smart cities represent a modern urbanization concept that leverages information and communication technology to enhance efficiency and quality of urban life. The transformation towards smart cities involves the integration of advanced technology, big data, and analytics to modernize urban infrastructure, such as transportation systems, energy, and public services. The primary goal of this research is to analyze how effective leadership can influence innovation and business performance in the infrastructure sector within the context of smart cities, as well as to provide insights into strategies and best practices that can be applied to achieve optimal outcomes. This study employs a literature review method with a qualitative approach and descriptive analysis. Data was gathered from Google Scholar for the period 2016 to 2024, aiming to collect and evaluate the latest articles relevant to the research topic. The study’s findings indicate that effective leadership plays a key role in guiding and implementing smart city technologies, which, in turn, enhance innovation and performance in the infrastructure sector. The implementation of smart city technologies, such as smart traffic management systems and energy solutions, has proven to increase operational efficiency, sustainability, and the quality of life for citizens. Collaboration between government, the private sector, and the community is also found to be crucial in achieving optimal results from smart city transformations.